PERLINDUNGAN KONSUMEN TERHADAP PRODUK MAKANAN TANPA SERTIFIKASI HALAL YANG DIJUAL MELALUI MEDIA LAYANAN GOFOOD - Aris Firman Hidayat; Rosalinda Elsina Latumahina (Gapenas Publisher, 2022)
Cases of rampant problems regarding halal-labeled food products in Indonesia that are not yet clear about their halal status, show that various products in Indonesia have included a halal label on a product, but the product does not have halal certification from the Ministry of Religion, which means that the initiative from the producer, so that the product is not yet clear about its halal. In this increasingly modern era with all the technology, there has been a change in the marketing of a food product, especially for the Indonesian people, with this technology making everything in society faster and more efficient, including in terms of food marketing. The existence of this technology has provided marketing opportunities for businesses to trade food products online. The online media that is often used by the public to meet their food needs is through the Gofood application service media. Because it can be a great opportunity to trade food products easily. In this research, it examines the laws and regulations relating to the halal food products sold through the Gofood service media